The exploration of health seeking behaviour of clients presenting with minor ailments attending community health centres in Khayelitsha (Michael Mapongwana, Site B) and Phillipi (Inzame Zabantu, Mzamomhle) - Mtwana, N B (Department of Medicine, 2014)
Includes bibliographical references.